Pengaruh Bauran Pemasaran 4P Terhadap Keputusan Konsumen Dalam Pemilihan Produk Kecap Pada Perusahaan Kecap Cap Udang Purwodadi - , RISMA RACHMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ketchup stamp Purwodadi shrimp sauce is not the only local circulating Grobogan, but the soy sauce already has a name in the market without any promotion of the company in real terms, because the promotion is only done directly from mouth to mouth. This evaluation is motivated by reasons consumers prefer to buy soy sauce stamp shrimp compared with other local. According to consumer opinion shrimp sauce cap has an advantage because it tastes. This evaluation aims to determine the characteristics of consumers who become stamp shrimp sauce and the reasons consumers choose to buy a stamp shrimp sauce. Evaluation was conducted by using the tools in the form of questionnaires, samples taken by 30 respondents. Questionnaires were made to obtain information on the characteristics of respondents who consume soy shrimp Purwodadi stamp, an assessment of the variables of the marketing mix (product, price, place, promotion) regarding soy products Purwodadi shrimp stamp, and stamp the respondents' knowledge about soy shrimp Purwodadi. Analysis of the questionnaire was done by scoring techniques and qualitative descriptions, as well as to test the questionnaire using validity and reliability testing. Based on the evaluation results of the consumer decides to buy a stamp shrimp soy products of variable products because soy sauce has a black color, in terms of price cap shrimp sauce consumer choice because it is in conformity with the contents, in terms of the distribution of soy sauce shrimp have been distributed stamp is only done in the District Grobogan so these products easily available in the shop or store located in Grobogan, and in terms of the promotion of soy products have been stamped shrimp promotion done directly one with the brand that is easily recognizable, pronounced and remembered by consumers.